How the toughest inorganic fullerene cages absorb shockwave pressures in a protective nanocomposite: experimental evidence from two in situ investigations - Xu, Fang; Kobayashi, Takamichi; Yang, Zhuxian; Sekine, Toshimori; Chang, Hong; Wang, Nannan; Xia, Yongde; Zhu, Yanqiu (American Chemical Society, 2017)
Nanocomposites fabricated using the toughest caged inorganic fullerene WS2 (IF-WS2) nanoparticles could offer ultimate protection via absorbing shockwaves; however, if the IF-WS2 nanomaterials really work, how they behave and what they experience within the nanocomposites at the right moment of impact have never been investigated effectively, due to the limitations of existing investigation techniques that are unable to elucidate the true characteristics of high-speed impacts in composites. We first fabricated Al matrix model nanocomposites and then unlocked the exact roles of IF-WS2 in it at the exact moment of impact, at a time resolution that has never been attempted before, using two in situ techniques. We find that the presence of IF-WS2 reduced the impact velocity by over 100 m/s and in pressure by at least 2 GPa against those Al and hexagonal WS2 platelet composites at an impact speed of 1000 m/s. The IF-WS2 composites achieved an intriguing inelastic impact and outperformed other reference composites, all originating from the “balloon effect” by absorbing the shockwave pressures. This study not only provides fundamental understanding for the dynamic performance of composites but also benefits the development of protective nanocomposite engineering.